The incisive papilla as a guide to maxillary anterior teeth position for complete dentures - Rosalin Kar; Niranjan Mishra; Debashish Pati; Krishna Gopal Birmiwal; Aparna Gupta; Subhrajit Raut (Wolters Kluwer Medknow Publications, 2019)
Context: The incisive papilla as a guide for complete dentures. Aims: To evaluate incisive papilla as a guide to maxillary anterior teeth position for complete dentures. Settings and Design: To measure the linear distances from the incisive papilla to the maxillary central incisors in Odia population and compare it to other ethnic groups. Subjects and Methods: The subjects were selected following inclusion & exclusion criteria. The impressions of maxillary & mandibular arches were taken and poured with die stone to produce the cast. The incisive papilla & incisors were marked on casts with a pencil. The photographs of casts were traced on an acetate tracing paper. The anterior-most points of maxillary incisors, anterior, middle & posterior-most points of incisive papillae were marked on the tracing as A, I1,M, I2 respectively. The A to M and A to I2 distances were measured, analysed and compared with Caucasians, Southern Chinese, and Dravidians. Statistical Analysis: Independent sample "t" test and Analysis of Variance followed by the post-hoc Bonferroni test were used. Results: A sample of 100 subjects in the age group of 20 to 40 years with was selected. The A to M measurements of Odia population differed significantly from Caucasians but were similar to Southern Chinese population. The A to I2 measurements of Odia population differed significantly from Caucasians & Dravidians but were similar to Southern Chinese. Conclusion: The linear measurements from incisive papilla to maxillary incisors of the Odia population are similar to that of Southern Chinese but differ significantly from Caucasians and Dravidians.